PENGELOLAAN SDM BERBASIS KNOWLEDGE MANAGEMENT DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM - Maila Rosidah rosidah; Zainal Berlian; Baharuddin (STKIP Subang, 2026)
This study examines the role of human resource management based on knowledge management in improving the quality of Islamic education. The research is motivated by the need for adaptive and knowledge-based management in educational institutions amid globalization and digital transformation. This study aims to analyze how the integration of knowledge management in human resource management contributes to sustainable educational quality improvement. The research employs a qualitative approach using a library research method by reviewing relevant literature, including books, journals, and previous studies. The findings indicate that knowledge management plays a strategic role in enhancing teachers' competencies through processes of knowledge creation, storage, sharing, and application. The implementation of knowledge management encourages collaboration, innovation, and continuous learning within educational institutions. However, several challenges remain, such as the lack of knowledge-sharing culture, limited technological infrastructure, and insufficient leadership support. Therefore, strengthening organizational culture, improving digital literacy, and optimizing leadership roles are essential to ensure effective implementation. In conclusion, human resource management based on knowledge management significantly contributes to improving the quality of Islamic education in a holistic and sustainable manner.